Insulin-induced mTOR signaling and gluconeogenesis in renal proximal tubules: A mini-review of current evidence and therapeutic potential - Nakamura, Motonobu; Satoh, Nobuhiko; Horita, Shoko; Nangaku, Masaomi (Frontiers in Pharmacology, 2022)
Energy is continuously expended in the body, and gluconeogenesis maintains glucose homeostasis during starvation. Gluconeogenesis occurs in the liver and kidneys. The proximal tubule is the primary location for renal gluconeogenesis, accounting for up to 25% and 60% of endogenous glucose production during fasting and after a meal, respectively. The mechanistic target of rapamycin (mTOR), which exists downstream of the insulin pathway, plays an important role in regulating proximal tubular gluconeogenesis. mTOR is an atypical serine/threonine kinase present in two complexes. mTORC1 phosphorylates substrates that enhance anabolic processes such as mRNA translation and lipid synthesis and catabolic processes such as autophagy. mTORC2 regulates cytoskeletal dynamics and controls ion transport and proliferation via phosphorylation of SGK1. Therefore, mTOR signaling defects have been implicated in various pathological conditions, including cancer, cardiovascular disease, and diabetes. However, concrete elucidations of the associated mechanisms are still unclear. This review provides an overview of mTOR and describes the relationship between mTOR and renal.